Sistem Monitoring Produksi Menggunakan Laravel Dan Cork-Bootstrap - Abim Ari Bimantara; Rakhmat Dedi Gunawan (Journal of Information Technology, Software Engineering and Computer Science, 2023)
PT Perkebunan Nusantara VII (PTPN 7) is a leading plantation company in Indonesia that produces main agricultural commodities. The PDF-based daily production data processing process is still done manually, takes time, and does not support interactivity. This research introduces a web-based Production Monitoring System which enables more efficient and faster monitoring of production results. This system uses crawling techniques to collect production data and presents it in graphic form that can be accessed via a web platform. Apart from that, this system is equipped with a Geographic Information System (GIS) feature to provide information regarding the location of the garden. The system development method uses the Extreme Programming method and system development uses Laravel with a template from Cork - Bootstrap 5. The main objective of this research is to build a Web Production Monitoring system that can help PTPN 7 monitor production results in a quickly updated manner. The results of the ISO 25010 testing that has been carried out conclude that the service quality of the resulting system has a good percentage of success with a total average of above 88%.